Definitiveness and operationality of dissociation - Jörn Altmann (Intereconomics, 1981)
While the traditional export promotion and import substitution strategies have largely failed to boost development in the Third World, rigorous dissociation from the industrialized countries cannot be regarded as a realistic strategy either. More promising seems a combination of partial dissociation from the North and increased cooperation between the developing countries themselves.
Keywords: 330; Dissociation